The role of the home in relation to the current teenage problem in the city of Manila - Fabillar, Restituto F. 1924- (1958)
This study delves into the relation of homes and the various growing problems among teenagers. The normative survey method of research was used. It was found that the home had significant roles in meeting the physical health, emotional, social, and spiritual needs of adolescents.
Thesis (M.A.)--University of the Philippines, Diliman.
Keywords: Home; Adolescence; Juvenile delinquency -- Philippines -- Manila